Milk, money, and gender: Exploring the link between women's decision-making in dairy production and welfare investments in boys versus girls - Jessie Lin; Meike Wollni (Canadian Journal of Agricultural Economics/Revue canadienne d'agroeconomie, 2024)
Greater women's bargaining power and decision-making within a household have been shown to increase investments in human capital. This study links women's participation in decision-making in dairy production with household investment in girls and boys in health, nutrition, and education. We survey households in the urbanizing region of Bangalore, India. We utilize a multinomial treatment effects model to analyze the individual and household factors that are associated with women's participation in sole or joint decision-making. We then assess how the type of decision-making influences a household's investments. The results first show that female decision-making households are more disadvantaged on average than other types of decision-making households. Second, we observe that female decision-makers for dairy production are more likely to have more children and earn a higher income than their husbands. Third, the main findings show that households in which women engage in joint decision-making have higher levels of investment across all categories for girls. Conversely, investments decrease in education and nutrition for both girls and boys when the wife is the sole decision-maker. Lastly, investments are enhanced further for girls when households can sell milk at a higher price.
Keywords: 330; children's investments; dairy production; decision-making; gender; India